The Kerala model 25 years later. Lessons in Covid times - Cairó-i-Céspedes, Gemma (REVESCO. Revista de Estudios Cooperativos, 2023)
The Indian state of Kerala, recognized for its model of human development whose achievements are far from the rest of India and the developing world, has been able to successfully deal with Covid despite the adverse conditions that the region faced. The legacy of the Kerala model, especially the availability of a primary care public health system and high educational levels, together with an effective public action where a proactive state and an organized society are fed back, explain the good results in containment of the Covid pandemic, as well as in alleviating its socioeconomic impacts.
Keywords: Kerala model; Covid; Human development; Public action; Cooperation